2007
DOI: 10.1002/joc.1601
|View full text |Cite
|
Sign up to set email alerts
|

On ENSO impacts on European wintertime rainfalls and their modulation by the NAO and the Pacific multi‐decadal variability described through the PDO index

Abstract: While strong relationships have previously been established between the El Niño/Southern Oscillation (ENSO) and climate variability in many parts of the world, previous analyses of ENSO impacts on European rainfalls have been variable and inconclusive. In this paper, the role and apparent interactions of a range of known teleconnections are assessed. It is shown that ENSO events do indeed appear to impact European rainfalls and that these impacts are likely to also depend on the concurrent state of the North A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 52 publications
6
52
0
2
Order By: Relevance
“…As stated before, some authors have attributed this changing impact to the influence on the atmospheric mean state of well-known multidecadal SST modes such as the AMO and the Interdecadal Pacific Oscillation (IPO, [20,136]). This seems to be crucial for those regions where the skill of seasonal forecasting systems is still poor, as is the case of Europe and the Mediterranean region.…”
Section: Impact Of Enso On Anomalous Rainfallmentioning
confidence: 91%
“…As stated before, some authors have attributed this changing impact to the influence on the atmospheric mean state of well-known multidecadal SST modes such as the AMO and the Interdecadal Pacific Oscillation (IPO, [20,136]). This seems to be crucial for those regions where the skill of seasonal forecasting systems is still poor, as is the case of Europe and the Mediterranean region.…”
Section: Impact Of Enso On Anomalous Rainfallmentioning
confidence: 91%
“…The PDO is defined by Mantua et al (1997) and Zhang et al (1997) as the leading principal component of the monthly sea surface temperature (SST) variability poleward of 20°N after removal of global mean SST. The PDO has generally been linked to climate changes around the Pacific basin (Mantua and Hare, 2002), but (Zanchettin et al, 2008) have argued that the influence of ENSO on European climate is generally more pronounced during positive phases of PDO, thus we will consider its potential role on the records of Croatian climate.…”
Section: Introductionmentioning
confidence: 99%
“…ENSO's influence in Europe generally, and perhaps the Mediterranean also, is more pronounced when the PDO (Zanchettin et al, 2008) is in a positive phase. As an example of this variable connection between ENSO and Mediterranean climate, Broennimann (2007) showed that the El Niño events of 1941-1942 and 1983 are associated with fairly different responses as seen in winter precipitation throughout this region.…”
Section: Introductionmentioning
confidence: 99%
“…negative phase) in both hemispheres of the Pacific Ocean (Folland, 2002) and are known to influence climate patterns around the world (e.g. Kiem et al, 2003;Kiem and Franks, 2004;Verdon et al, 2004;Zanchettin et al, 2008). Importantly the IPO/PDO has been found to be a dominant climate mode in the Pacific sector since at least the 15th Century (Verdon and Franks, 2006) and is therefore likely to continue to influence climate in the future.…”
Section: Introductionmentioning
confidence: 99%